2007
DOI: 10.1128/mcb.00996-06
|View full text |Cite
|
Sign up to set email alerts
|

Helix-Loop-Helix Protein p8, a Transcriptional Regulator Required for Cardiomyocyte Hypertrophy and Cardiac Fibroblast Matrix Metalloprotease Induction

Abstract: Cardiomyocyte hypertrophy and extracellular matrix remodeling, primarily mediated by inflammatory cytokine-stimulated cardiac fibroblasts, are critical cellular events in cardiac pathology. The molecular components governing these processes remain nebulous, and few genes have been linked to both hypertrophy and matrix remodeling. Here we show that p8, a small stress-inducible basic helix-loop-helix protein, is required for endothelin-and ␣-adrenergic agonist-induced cardiomyocyte hypertrophy and for tumor necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 50 publications
2
65
0
1
Order By: Relevance
“…Although these different scenarios require further study, the required role of the c-Jun binding activity in p38␥ stimulating c-Jun synthesis, MMP9 transcription, and invasion highlights an essential role of this protein-complex in triggering the invasion cascade. c-Jun was previously shown to bind the MMP9 promoter in cardiac (50) but not in neuronal cells (51), and similarly we showed that c-Jun only binds the MMP9 in the presence of p38␥, indicating a determinant role of c-Jun cofactor abundances in its trans-activation of MMP9. Our results suggest that p38␥ may be one of these critical cofactors to determine c-Jun transcriptional activity by increasing its expression and facilitating its target gene promoter binding.…”
Section: P38␥ Stimulates C-jun and Mmp9 Transcriptionmentioning
confidence: 58%
“…Although these different scenarios require further study, the required role of the c-Jun binding activity in p38␥ stimulating c-Jun synthesis, MMP9 transcription, and invasion highlights an essential role of this protein-complex in triggering the invasion cascade. c-Jun was previously shown to bind the MMP9 promoter in cardiac (50) but not in neuronal cells (51), and similarly we showed that c-Jun only binds the MMP9 in the presence of p38␥, indicating a determinant role of c-Jun cofactor abundances in its trans-activation of MMP9. Our results suggest that p38␥ may be one of these critical cofactors to determine c-Jun transcriptional activity by increasing its expression and facilitating its target gene promoter binding.…”
Section: P38␥ Stimulates C-jun and Mmp9 Transcriptionmentioning
confidence: 58%
“…Similar to MyoD, p8 is acetylated by p300, which leads to enhanced transcriptional activity of associated tissue-specific factors such as Pax2 (Hoffmeister et al, 2002). Analysis of p8 secondary structure predicts a HLH motif (Goruppi et al, 2007) towards the C-terminus (positions 46-71), suggesting the potential to dimerize with other HLH proteins, including MyoD (Murre et al, 1989;Benezra et al, 1990). However, the importance of the HLH motif is unresolved because our preliminary studies suggest that overexpression of a mutant p8 lacking helix 2 mimics wild-type p8 in inhibiting the cell cycle as well as MyoD and myogenin expression (S.C., unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Partners of p8: p300, p68 and MyoD p8 shares 35% amino acid identity with the HMGA1 (formerly HMGI/Y) chromatin architectural factors (Encinar et al, 2001) and can regulate the activity of different transcription factors, such as Smad (Garcia-Montero et al, 2001), p53 (Clark et al, 2008), Jun and other established AP1 effectors (Goruppi et al, 2007). p8 also binds to p300 and Pax2-transactivation domain interacting protein (PTIP) to regulate the activity of Pax2A and Pax2B on the glucagon promoter (Hoffmeister et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we show that TEAD4 directly regulates expression of NUPR1 that is required for endothelin-and a-adrenergic agonist-induced cardiomyocyte hypertrophy. 31 Moreover, NUPR1 negatively regulates cardiomyocyte autophagy. Dysfunctional autophagy has been linked to cardiomyopathies and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%